A new species of Leptolalax (Anura: Megophryidae) from the sacred groves of Mawphlang, Meghalaya, north-eastern India - Das, I.; Tron, R.K.L; Rangad, D.; Hooroo, R.N.K (Zootaxa, 2010)
A new species of megophryid frog of the genus Leptolalax is described from the sacred groves of Mawphlang, East Khasi Hills, north-eastern India. L. khasiorum new species, is compared with congeners from India and other parts of south-east Asia. The new species is diagnosable in showing the following combination of characters: SVL 24.5–27.3 (mean 25.63 ± 0.61 SE) mm in a sample of four adult males; 31.2–33.4 (mean 32.50 ± 0.67 SE) mm in a sample of three females; dorsum with fine scattered tubercles; eyelids with tubercles; tympanum and supratympanic fold distinct; macroglands, including preaxillary, pectorals and ventrolateral glands present; Finger I > II; toe tips not dilated, bearing dermal fringes; dorsum with dark blotches; flanks with large dark blotches; dark tympanic mask present; venter lacking dark blotches; labial bars present and limbs with dark cross-bars.